Gender differences in alcohol use disorder: evaluation the inpatient treatment data - Evren, E. Cüneyt; Saatçioğlu, Ömer; Evren, Bilge; Yapıcı, Aslıhan; Çakmak, Duran (Journal of Dependence, 2003)
Objective: The aim of this study was to compare sociodemographic and alcohol use related characteristics of inpatients with alcohol use disorder according to the gender.Method: Semistructured sociodemographic form, which also included questions about substance use characteristics, was applied to 3851 patients who had inpatient treatment at the AMATEM clinic between the years of 1998 and 2002.Results: The mean age of the female users was (40.78±10.17) lower than the mean age of male users (45.99±9.33). Among female patients, ratios of being divorced and single, unemployed, having high education status, suicide attempt history and alcohol and drug use in family were high. Among male patients having trouble with criminal justice related to alcohol use, dangerous and harmful behaviors while intoxicated, and imprisonment history were high.Conclusion: Female and male alcohol using patients differ according to some of the characteristics. These findings suggest that gender differences must be taken in to consideration in alcohol use disorder.
Keywords: Alcohol use; gender; inpatient treatment